PENGARUH PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL DI PT TRI MANDIRI SELARAS CABANG SINTANG - Magdalena, Lin (Universitas Kapuas Sintang, 2025)
This study uses quantitative research methods. In this study, the population is consumers who buy cars in 2023, totaling 420 people. The number of samples is 81 people. The variables in this study are two independent variables, namely X1 (Service), X2 (Price), and the dependent variable, namely Y (Purchase Decision). The measurement instrument in this study uses a Likert scale. Data collection techniques use questionnaires, observation and documentation. The data in this study will be processed and calculated using the SPSS program. In this study, validity tests, reliability tests, multiple linear regression hypothesis tests, partial tests (t tests), simultaneous tests (F tests), determination coefficient tests (r2) will be carried out. The results of this study indicate that the instruments used in variables X1, X2, Y are declared valid because r count> r table and are declared reliable because Cronbach Alpha (ɑ) variables X1 = 0.815, X2 = 0.765 and Y = 0.615 are greater than 0.6. The multiple linear regression hypothesis test obtained the regression equation results, namely Y = 3.655 + 0.007 + 0.825. The F test results of the hypothesis of variable X1 are Ho rejected and Ha accepted because f Count 522.157 > f Table 3.114 meaning that Service and Price together influence the Decision to Purchase a car at PT Tri Mandiri Selaras Sintang Branch. The T test produces variable X1 has a significance value of 0.627 > 0.05 and a t Count value of 0.488 < t Table 1.99085. So the hypothesis is Ho accepted and Ha rejected meaning that X1 does not affect Y (Purchase Decision) of cars at PT Tri Mandiri Selaras Sintang Branch. Variable X2 has a significance value of 001 < 0.05 and a t Count value of 31.58 > t Table 1.99085. So the hypothesis is Ho is rejected and Ha is accepted, meaning X2 (Price) has an effect on Y (Purchase Decision) of cars at PT Tri Mandiri Selaras Sintang Branch. The analysis of the determinant coefficient results in the R Square value = 0.931, meaning that the variables X1 (Service) and X2 (Price) have an effect on the variable Y (Purchase Decision) of 0.931 or 93.1% while the remaining 6.9% is influenced by other variables not examined in this study.